Effect of oxygen terminated surface of boron-doped diamond thin-film electrode on seawater salinity sensing. (30th September 2021) - Shi, Dan; Liu, Lusheng; Zhai, Zhaofeng; Chen, Bin; Lu, Zhigang; Zhang, Chuyan; Yuan, Ziyao; Zhou, Meiqi; Yang, Bing; Huang, Nan; Jiang, Xin
Graphical abstract: Highlights: Oxygen terminated BDD electrodes demonstrate high sensitivity and great long-term stability in seawater salinity detection. The high sensitivity of the oxygen terminated BDD electrodes can be ascribed to the improved Cdl which is enhanced by C-O functional group. Oxygen terminated BDD electrodes display outstanding stability thanks to the stable exist of surface oxygen. Excellent oxygen terminated BDD electrodes promise potential application in practical seawater salinity detection. Abstract: Tremendous demands for highly sensitive and stable seawater salinometers have motivated intensive research on advanced electrode materials. Boron-doped diamond (BDD) is attractive in terms of its high mechanical stability and chemical inertness, but is usually hindered by its low double-layer capacitance ( C dl ) for seawater salinity detection. Here, inspired by the principle of oxygen-terminated BDD electrode endowing higher C dl than hydrogen-terminated surface, we introduce the oxygen terminated surface by oxygen plasma or reactive ion etch (RIE), and the fabricated oxygen terminated BDD electrodes demonstrate high sensitivity and long-term stability in seawater salinity detection comparing with the hydrogen terminated BDD electrodes. Significantly, the as-fabricated O-BDD-RIE electrodes not only show remarkable enhanced response even better than the commercial platinum black electrodes but also display long-time stability which is weekly verified by continuous monitor for 90 days. The outstanding performance of the oxygen terminated BDD electrodes can be ascribed to the enhancement of C-O surface functional group on C dl . In addition, a comprehensive analysis of effective electroactive surface area (EASA) and C dl proves that the surface oxygen is the major factor for the improved C dl . In summary, the excellent oxygen terminated BDD electrodes promise potential application in seawater salinity detection.